Epidemiological study of asymptomatic inflammatory bowel disease: the identification of cases during a screening programme for colorectal cancer. Issue 4 (April 1989) - Mayberry, J F; Ballantyne, K C; Hardcastle, J D; Mangham, C; Pye, G
Abstract : An asymptomatic population of 37, 000 people in the Nottingham area were offered faecal occult blood tests in a screening study for colorectal cancer. Seventeen thousand nine hundred and thirty people completed the tests and 481 individuals with positive tests underwent full investigation of the colon. Eight people with previously undiagnosed inflammatory bowel disease were identified. In five cases there was total ulcerative colitis; in one a proctitis and in two Crohn's disease. Two further patients with ulcerative colitis were identified; they had been lost to follow up for 25 and 45 years respectively. The combined prevalence of inflammatory bowel disease was 56/10(5) and it is likely that current studies of the epidemiology of these conditions may underestimate the true prevalence by between 27% and 38%.